The artificial generation of the equilibrium marine atmospheric boundary layer for the CFD simulation of offshore wind turbines. Issue 183 (December 2018) - Liu, Yichao; Chen, Daoyi; Li, Sunwei
Abstract: Computational fluid dynamics (CFD) technique has been widely used in simulating dynamic responses of offshore floating wind turbines under excitations of prescribed wave and wind loads. In the simulation, the Volume of Fluid (VOF) method is generally employed to capture the free surface of the liquid, which illustratively shows the evolution of waves. The stresses at the free surface are not explicitly modeled in the VOF method, which challenge the establishment of the equilibrium marine atmospheric boundary layer (MABL) throughout the computational domain. Given the importance of the generation of the MABL in a CFD simulation of offshore wind turbines, methods for establishing sustainable wind profiles in a simulation based on the VOF method should be systematically investigated. In the present study, a virtual body force method is developed to maintain the horizontally homogeneous MABL in the VOF-based CFD simulation. The proposed method is quantitatively verified through a simulation of the equilibrium MABL with the sheared wind profile. Highlights: A virtual body force method is developed to maintain the horizontally homogeneous MABL in the VOF-based CFD simulation. The proposed approach is quantitatively verified by several CFD simulations of the equilibrium MABL. Power-law engineering models are proposed to specify the inlet boundary conditions for maintaining the equilibrium MABL. Empirical parameters are suggested to define the power-law models according to U 10 and H .